Leadership Capabilities and Challenges in the Physiotherapy Profession in Ireland - MCGOWAN, EMER (Trinity College Dublin. School of Medicine. Department of Physiology, 2017)
The physiotherapy profession in Ireland is experiencing a period of transition and change and is facing many challenges. The importance of leadership in healthcare has been recognised, however, to date there has been little research examining leadership in the profession of physiotherapy. The aim of this PhD thesis was to explore perceptions of leadership capabilities among physiotherapists in Ireland and to identify the leadership challenges facing the physiotherapy profession. A scoping review was conducted to explore the literature on leadership in physiotherapy. This review concluded that leadership in physiotherapy is an under-researched phenomenon but interest and research in the field are growing. In the first study of this thesis, members of the Irish Society of Chartered Physiotherapists (ISCP) were surveyed about leadership and leadership development. The results demonstrated that physiotherapists in Ireland perceive communication and professionalism to be the most important leadership capabilities. A high percentage of the respondents perceived themselves to be a leader (74%) and the majority (53%) rated attaining a leadership position as very important or extremely important. Formal leadership training had been completed by 24.7% of respondents and informal leadership training had been completed by 32.8% of respondents. Participation in leadership development training was found to be associated with self-declaration as a leader and with placing importance on attaining a leadership position. The first study demonstrated the leadership capabilities that the general physiotherapy population perceive to be important. The leadership capabilities of a specific cohort of potential physiotherapy leaders, physiotherapy managers, were investigated in the second study. This study was based on the leadership framework of Bolman and Deal (1991, 2008). In phase 1 of the study, physiotherapy managers were surveyed using the Leadership Orientations Survey. Results of the survey demonstrated that the physiotherapy managers used the human resource frame most often followed by the structural frame. Most respondents used only one frame or no frames at all and only a small number were found to use three or four frames. In keeping with the theory of Bolman and Deal, a statistically significant trend was found between the number of frames that a manager uses and their perceived effectiveness as a manager and as a leader. To explore the leadership capabilities of physiotherapy managers in more detail, in phase 2 of the second study semi-structured interviews were conducted with a purposive sample of physiotherapy managers. Analysis of these interviews demonstrated that the managers predominantly used leadership capabilities associated with the human resource and structural frames. The managers’ use of the political frame was more varied, some leadership strategies and behaviours associated with the political frame were reported, however there were also difficulties reported with capabilities in this frame. The symbolic frame was underused by the managers and there was less recognition of its importance. The managers in this study also identified challenges facing physiotherapy leaders and the physiotherapy profession. These challenges were: time constraints, lack of resources, other professions and changing structure. In study III, the leadership capabilities of another cohort of physiotherapy leaders, physiotherapy clinical specialists and APPs, were explored. Analysis of these interviews demonstrated that the clinical specialists/APPs also predominantly worked through the human resource frame. The clinical specialists reported consistent use of capabilities associated with the structural frame whereas there was less prevalent use of political and symbolic frame leadership capabilities. A common theme in these interviews, however, was the concept of leading by example which falls within the symbolic frame. The clinical specialists/APPs reported the same challenges as those identified by the physiotherapy managers but also identified two additional challenges: ordering images and career structure. In the final study, clinical physiotherapists’ perceptions of the leadership capabilities of physiotherapy management in their workplace were investigated. Clinical physiotherapists were sent a paper-based survey which asked them to rate both the importance of 24 leadership capabilities and the effectiveness of physiotherapy management in their workplace at demonstrating them. Results of the survey demonstrated that ratings of importance of the leadership capabilities were significantly higher than ratings of effectiveness. The greatest difference between ratings of importance and ratings of effectiveness were found on the symbolic frame capabilities. Physiotherapy management were rated as most effective on leadership capabilities associated with the structural and political frames. The results of this thesis suggest that physiotherapy managers and clinical specialists/APPs may benefit from training to further develop their leadership capabilities. This training should focus particularly on leadership capabilities associated with the symbolic frame. Further research is needed to guide the design and evaluation of these leadership development interventions.
PUBLISHED
Keywords: Physiotherapy; Leadership; Health service management; Health service management; Leadership; Physiotherapy